Fußprobleme beim Sportler - Biedert, R. M.; Arnold, M. P.; Delmi, M.; Friedrich, N. F.; Hintermann, B.; Zollinger, H. (Sport-Orthopädie - Sport-Traumatologie, 2001)
Foot problems in sports are diverse and sportspecific with numerous underlying etiologies. The presented disorders (hallux valgus and rigidus, plantarfasziitis, nerve compression syndromes, dysfunction of the tibialis posterior tendon, bone bruises) are in most cases due to overload. Specific investigations are necessary to determine both correct diagnosis and the successful treatment.